2017
DOI: 10.1039/c7py00561j
|View full text |Cite
|
Sign up to set email alerts
|

A general route to chiral nanostructures from helical polymers: P/M switch via dynamic metal coordination

Abstract: Macroscopically enantiomeric chiral nanospheres made from P or M helical polymer metal complexes can be obtained via dynamic coordination chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…Substituted polyacetylenes can adopt helical structures under appropriate conditions. The macromolecular helical structures can be analyzed by circular dichroism (CD) and UV–vis absorption spectroscopy measurements . Noteworthily, the optical activity of substituted polyacetylenes can be quantitatively measured in solution state, but only qualitative characterizations can be performed on the products in the form of particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituted polyacetylenes can adopt helical structures under appropriate conditions. The macromolecular helical structures can be analyzed by circular dichroism (CD) and UV–vis absorption spectroscopy measurements . Noteworthily, the optical activity of substituted polyacetylenes can be quantitatively measured in solution state, but only qualitative characterizations can be performed on the products in the form of particles.…”
Section: Resultsmentioning
confidence: 99%
“…The macromolecular helical structures can be analyzed by circular dichroism (CD) and UV-vis absorption spectroscopy measurements. [16][17][18][19][20][21][22][23][24][25] Noteworthily, the optical activity of substituted polyacetylenes can be quantitatively measured in solution state, but only qualitative characterizations can be performed on the products in the form of particles. Referring to our previous studies, [15] polymers derived from M-1 and M-2 adopted helical conformations but without optical activity, that is, the products are racemic helical polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore,o nce the presence of the chiral conflict was established, we decided to explore the dynamic behavior of these copolymers by studying their interaction with metal ions (that is,e xternal stimuli)i nT HF.I np revious reports,i ti s found that poly-(R)-1 adopts an M helix in the presence of monovalent metal ions,while a P helix is induced by divalent ones (Figure 4a). [33][34][35][36][37] On the other hand, poly-(R)-2 stabil-izes an M helix in the presence of both types of ions (Figure 4b). [38,39] Owing to the active chiral conflict in the copolymer, it was expected that the different interactions of the comonomers with the ions could either enhance acertain helical sense;for example, m-(R)-2 inverts its helical sense from P 2 to M 2 ,while m-(R)-1 keeps its M 1 helical structure;that is,anexcess of M helicity (Figure 4c), or generate another axially racemic copolymer mirror image of the original one,f or example, m-(R)-1 goes from M 1 to P 1 and m-(R)-2 from P 2 to M 2 ;that is,f rom axially racemic 1 to axially racemic 2 (Figure 4c), through the mechanisms shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Moreover,these two types of homopolymers respond in different ways to monovalent and divalent metal ions. [31][32][33][34][35][36][37][38] Hence,i fe ach monomer retains independently its ability to respond to these stimuli within the copolymer without being affected by the presence of the other chiral monomer,anovel sensor material with better properties than the parent homopolymers could be generated based on the chiral conflict effect depicted above.…”
mentioning
confidence: 99%
“…4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 Riguera, Freire et al [17] achieved the goal of simultaneous adjustment of size and helical sense of CPPs derived from axially racemic poly(phenylacetylene) in chloroform, and the role of the secondary structure of helical poly(phenylacetylene)s was investigated. [57] As shown in Figure 8, ions with different valence were used as chiral inducer and cross-linking agent. The size of CPPs was tuned by the polymer/ion ratio while the helical sense is modulated by the polymer/cosolvent ratio.…”
Section: Cpps Constructed By Racemic Helical Polymersmentioning
confidence: 99%